2017
DOI: 10.1111/jace.15355
|View full text |Cite
|
Sign up to set email alerts
|

Use of ceramic industry milling and glazing waste as an active addition in cement

Abstract: The beneficial effects of pozzolans on cement manufacture have encouraged their use in that industry. Traditional natural pozzolan have become less available of late, however, due to a decline in quarrying intensity aimed at minimizing the impact on the landscape. At the same time, environmental policies pursue the reduction or elimination of spoil heaps by valorizing industrial waste and by-products as raw materials, in keeping with the principles of the circular economy.The quest for new types of waste and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…The Si replacement by Al in the gel led to lower Ca/Si ratios (1.72). The foregoing was consistent with premises set out by other authors as well as with earlier results for the CS/Ca(OH) 2 system and cements containing granite sludge, in which the addition of pozzolans led to lower Ca/Si ratios than found in OPC.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The Si replacement by Al in the gel led to lower Ca/Si ratios (1.72). The foregoing was consistent with premises set out by other authors as well as with earlier results for the CS/Ca(OH) 2 system and cements containing granite sludge, in which the addition of pozzolans led to lower Ca/Si ratios than found in OPC.…”
Section: Resultssupporting
confidence: 92%
“…X‐ray diffraction analyses conducted in an earlier study showed the main crystalline phases in the CS to be: quartz, kaolinite, muscovite, illite, hematite, magnetite, calcite, dolomite, albite, and zircon (zirconium silicate).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations